The Effectiveness of “Undercover Anti-Bullying Teams” as Reported by Participants - John Winslade; Michael Williams; Felipe Barba; Evelyn Knox; Harpreet Uppal; Juanita Williams; Lorraine Hedtke (Interpersona: An International Journal on Personal Relationships, 2015)
An analysis of archival data retrieved from a school counselor’s careful recording of student responses during the conducting of 35 “undercover anti-bullying teams” reveals a highly positive qualitative account of the success of these teams. A targeted, non-punitive, restorative process calls forth peer influence to transform the bullying relation in a short time-frame. The bullies are involved in the transformation and the victim is never required to confront the bullies. Student responses show that participants value the chance to help a peer, take up the responsibility of stopping bullying responsibly, and victims are happy with the results.